Оцінка потенціалу джерел низькопотенційної теплоти для теплонасосних установок систем централізованого теплопостачання - Derii , Volodymyr; Sokolovska , Irina; Teslenko , Oleksandr (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
Methodology and calculation formulas are proposed for estimating the thermal potential and its distribution by the regions of Ukraine for natural and artificial (anthropogenic) low-grade heat sources: ambient air, ventilation emissions of buildings connected to district heating systems, soils and groundwater, large rivers, wastewater, waste heat of boilers and CHPs, and industrial waste heat. The availability of thermal potential of these sources for heat pump plants of district heating systems has been determined. Annual heat potential and average annual capacity were estimated for each of these sources. It is shown that the annual heat potential and average annual capacity available for heat pump plants in district heating systems are: 9,735 thous. Gcal and 905 MW for ambient air; 25,655 thous. Gcal and 1,871 MW for ventilation emissions of buildings; 2,628 thous. Gcal and 87 MW for soil and groundwater; 3,212 thous. Gcal and 299 MW for large rivers; 4,545 thous. Gcal and 338 MW for wastewater; 2,459 thous. Gcal and 724 MW for waste heat of boilers and CHPs; 7,661 thous. Gcal and 214 MW for industrial waste heat, respectively. The total thermal potential of the above-mentioned sources is 4.97 GW which enables the use of heat pump plants in district heating systems with a total capacity of about 7.5 GW. In the case of heat pump plants using low grade heat sources of natural origin, it must be taken into account that their intensive use can lead to their rapid thermal exhaustion and a significant impact on the environment. Therefore, it is necessary to maintain such level of energy use of natural low grade heat sources that would enable their exploitation without harming the environment. In the conditions of densely built-up cities of Ukraine, the use of heat of the soil and groundwater for heat pump plants will be limited due to the shortage of free land plots. It will also be problematic to use powerful air heat pump plants in populated areas due to their high noise level.